SETTING DALAM NOVEL EDENSOR KARYA ANDREA HIRATA - Ratna Kharisma; Syafrial '; Hadi Rumadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This Research entitle Setting in Novel Edensor Masterpiece Andrea Hirata. checked Problem go together this research ( 1) how physical setting in Edensor Andrea Hirata masterpiece novel, ( 2) how neutral setting in Edensor Andrea Hirata masterpiece novel, ( 3) how spritual setting in Edensor Andrea Hirata masterpiece novel, ( 4) how typical setting in Edensor Andrea Hirata masterpiece novel. As for target of this research is to physical setting description at Edensor Masterpiece Andrea Hirata novel, neutral setting describe at Edensor Masterpiece Andrea Hirata novel, spritual setting describe at Edensor Masterpiece Andrea Hirata novel, typical setting describeat Edensor Masterpiece Andrea Hirata novel. used Method namely descriptive method. Doneconducted by Technique data collecting at this research use bibliography technique. Data taken away from a novel entitling Edensor Andrea Hirata masterpiece. Technique analyse data this research use three step. The first , data discount that is identify data, throwing away data which is not needed, and important data classification in this research. Both, presentation of data and third of withdrawal final node. Setting represent one of the novel pembentuk element or can be conceived of intrinsic element. Setting cannot be studied separated with other element because representing one unity. As product one of art, novel play a part important in giving life attitude possibilities.Keywords: setting, novel, Andrea Hirata